P157 Follow-up of pulmonary nodules: following the fleischner radiology guidelines. (2nd December 2011) - Selvaraj, S; Parry, L; Garbett, K; McAdam, J; Naicker, T R; Srinivasan, K S; Moudgil, H
Abstract : Background: 0.1% of chest films and 1% of chest CT show incidental pulmonary nodule(s). While some of these are acted on immediately, others are followed up where the nodules are small and there are no risk factors (never smokers, age <35 years, other malignancies). Fleischner Society recommends interval CT follow-up of pulmonary nodules [MacMahon H et al, Radiology 2005], but whether we adhere to these is uncertain and presently we report our practices based on this. Methods: Over a 4-year period to July 2009, 145 of all cases discussed at our lung multidisciplinary (MDT) meeting had a pulmonary nodule(s). They are either considered for immediate action or subsequent follow-up. Mean (SD, range) year age for this cohort was 65 (11.04, 37 to 86) of which 82 were male and 63 female. Nodules were classified as single or multiple, and by initial size of the largest nodule where multiple. Results: Of the 145 cases, 97 had single nodule and 48multiple. Of these, respectively (n=absolute number) these were =4 mm (13), >4–6 mm (20), >6–8 mm (22), >8 mm (87) with do data in three. There were no follow-up data for 14, of whom 7 had refused subsequent follow-up, 4had been discussed at MDT but no more proposed, and three died. Where there were data for follow up, 69 (53%) followed Fleischner's guidelines on case selection and recommended interval scanning and 62 (47%) did not usually but not exclusively due to delayed imaging intervals. Classification by initial nodule size and whether appropriate follow-up or not and sub-divided by whether malignant or not is shown in the enclosed Abstract P157 table 1 (n=119, six still on active follow-up). Figures include those managed with PET scans whether under taken immediately (11) or later during follow-up (34). Of the entire cohort 28 had malignant disease of which 16 underwent surgery and 12 had an input through oncology. Of these, five had been identified as malignant because of increased size (2) or number (2) or because the nodule was persistent (1) but none had change in attenuation. Other cases where concerns were raised were benign (n=10) but were similarly being considered due to multiplicity of nodules (3), uncertainty (1) and a persistent opacity (1) but exact reasoning was not available in the five others. Conclusion: Data show that we conform to the Fleischner guidelines in approximately half the cases and these identified 15 who required further specific investigation and of which five had malignant disease. Although this is a small number of those followed up it supports the practice of follow-up but which still needs to better protocol driven.